The creation of a "new state" in Slovenia. Elaboration of the competences of public authorities and mobilization of social processes of identification and membership - a research program - Poche, Bernard (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 1993)
The author describes the general goals and the theoretical framework of a joint Franco-Slovene research project in sociology that will be launched in 1994 and will encompass various preselected field locations in Slovenia. The goal of the project is, by means of an ethnomethodological technique of analysis of the social representation, and a qualitative interpretation of results, to investigate the position, legitimacy, and the perception of the new Slovene state by its population.
Keywords: družbene razmere; družbeni procesi; država; državnost; geopolitika; regionalizem; Slovenija